Impact of Rehabilitation Interventions on Walking Endurance in Children with Cerebral Palsy. A Systematic Literature Review - Ieva Kavaliauskaitė; Jovita Petrulytė; Lina Budrienė; Juozas Raistenskis (Lithuanian Sports University, 2022)
Background. Decreased walking endurance in children with CP results in impaired gait function and adversely affects participation. Appropriate rehabilitation interventions can significantly increase walking endurance and associated functional efficiency. The aim. To evaluate the effectiveness of different rehabilitation interventions for walking endurance of children with CP by analyzing scientific research. Methods. The selection of articles was performed in the "PubMed" database, according to the keywords and criteria identifying the study topic. The selection scheme was performed according to the PRISMA guidelines. Results. 15 articles were included in the systematic review. Statistically significantly (p<0,05) higher walking endurance was found after: "Gait Trainer GT1" workout; muscle strength-power training; strength-endurance training + usual interventions (INT) and passive movement intervention, all compared to INT. Also, after: treadmill + INT (vs. walking + INT); treadmill with the "3DCaLT" robotic system (vs. treadmill); virtual reality with treadmill + INT (vs. treadmill + INT); whole-body vibration (vs. placebo). Conclusions. In children with cerebral palsy, certain gait training, muscle strength training, and passive movement interventions increase walking endurance more effectively compared to non-combined usual interventions. When choosing from several gait training interventions, the effectiveness of walking endurance training depends on the specifics of the intervention. Also, walking endurance is effectively enhanced by whole-body vibration (compared to placebo) and a virtual reality component combined with gait training (compared to the same intervention without a virtual reality component). Keywords: children, cerebral palsy, walking endurance, rehabilitation, systematic review.